2013
DOI: 10.1186/1472-6963-13-370
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation alongside a single RCT of an integrative psychotherapeutic nursing home programme

Abstract: BackgroundThere is an 80% prevalence of two or more psychiatric symptoms in psychogeriatric patients. Multiple psychiatric symptoms (MPS) have many negative effects on quality of life of the patient as well as on caregiver burden and competence. Irrespective of the effectiveness of an intervention programme, it is important to take into account its economic aspects.MethodsThe economic evaluation was performed alongside a single open RCT and conducted between 2001 and 2006. The patients who met the selection cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 46 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…Finally, in , Hakkaart‐van Roijen et al ., conducted a single RCT to perform the economic evaluation of an integrative psychotherapeutic nursing home programme: Integrative Reactivation and Rehabilitation (IRR). The results suggested that in IRR, patients improve more with regard to severity of multiple psychiatric symptoms (MPS), and caregivers improve on general burden and competence, with incremental costs varying from €130–€540 per additional point of improvement.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, in , Hakkaart‐van Roijen et al ., conducted a single RCT to perform the economic evaluation of an integrative psychotherapeutic nursing home programme: Integrative Reactivation and Rehabilitation (IRR). The results suggested that in IRR, patients improve more with regard to severity of multiple psychiatric symptoms (MPS), and caregivers improve on general burden and competence, with incremental costs varying from €130–€540 per additional point of improvement.…”
Section: Resultsmentioning
confidence: 99%